Epilogue: “And suddenly the memory revealed itself …”: making sense of the senses in history - Mittler, Barbara (Sensing China, 2022)
Starting with the symbolic Proustian moment of tasting the “petite madeleine,” the Epilogue provides a critical rethinking of the methodological significance of engaging history through the prism of the senses. By delving into and combining mental images, historical records, and fragmentary traces, we contemporary researchers are in some ways experiencing our own Proustian moments in reclaiming, reliving, or reflecting the sensuality of China’s cultural past. On the one hand, this chapter argues that the significance of our rekindled interest in the senses in historical writing lies in offering “flesh and blood” to historical figures and events, thus complementing a purely “rational” side of history writing. On the other hand, it also highlights the importance of taking into consideration this affective and sensory mapping of history. While it offers alternative, if subjective, non-absolute accounts of historical experience, including the sensory enriches the writing of history which, after all, will never be a definitive, unambiguous narrative “record” in the first place.